2008
DOI: 10.1245/s10434-007-9805-x
|View full text |Cite
|
Sign up to set email alerts
|

Resectable Well-Differentiated versus Dedifferentiated Liposarcomas: Two Different Diseases Possibly Requiring Different Treatment Approaches

Abstract: The biological behaviors of well-differentiated and dedifferentiated liposarcomas differ significantly. This article presents outcomes of two different surgical approaches that were implemented at the UTMDACC, treating these tumors as different disease entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 18 publications
1
89
0
10
Order By: Relevance
“…A dedifferentiated tumor tends to present more often as a recurrence, requires multi-organ resection more frequently, and has a shorter disease-free interval compared to those of well differentiated subtypes. Lahat et al [9] reported that 5-year relapse free survival of dedifferentiated liposarcoma was 7.8% compared to well differentiated type (41.9%), and overall survival rate of dedifferentiated and well differentiated type was 36.5% versus 92.1%. Therefore, in the cases of dedifferentiated liposarcoma, close follow up and careful surveillance are warranted for the detection of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…A dedifferentiated tumor tends to present more often as a recurrence, requires multi-organ resection more frequently, and has a shorter disease-free interval compared to those of well differentiated subtypes. Lahat et al [9] reported that 5-year relapse free survival of dedifferentiated liposarcoma was 7.8% compared to well differentiated type (41.9%), and overall survival rate of dedifferentiated and well differentiated type was 36.5% versus 92.1%. Therefore, in the cases of dedifferentiated liposarcoma, close follow up and careful surveillance are warranted for the detection of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate a more conservative approach when dealing with pure atypical lipomatous tumor given the very indolent biology of this disease. 13,14 In contrast, most authors agree that extended surgery is the treatment of choice for dedifferentiated liposarcoma. More liberal use of RT as well as chemotherapeutic agents, such as anthracyclines and/or trabectedin, is usually proposed for the few patients affected by primary myxoid/ round cell retroperitoneal liposarcoma given the observed sensitivity of this tumor to both RT and chemotherapy in large, retrospective series.…”
Section: Histological Subtypementioning
confidence: 99%
“…A recent nomogram based on 800 patients with liposarcoma has confirmed the importance of histological subtype. 1 Few would challenge the authors questioning of whether, with such different outcomes, treatment should be different; however, how different is different? The real challenge, alluded to in the title, is what ''different'' treatment should be applied to these ''different'' diseases.…”
Section: To the Editormentioning
confidence: 99%